2013
DOI: 10.1002/adsc.201300447
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Catalyzed Transvinylation – New Insights

Abstract: The use of ruthenium complexes in transvinylation catalysis has been well established since the 1980s. However, the reaction mechanism and the active catalyst species, which is presumed to contain ruthenium carbonyl carboxylate entities, have so far remained elusive. In this work the synthesis and characterization of three novel ruthenium complexes comprising ruthenium carbonyl carboxylate structural motifs including two single crystal structures as well as the crystal structures of two known ruthenium complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…While vinyl acetate is industrially produced by vapor‐phase acetoxylation of ethylene over Pd‐based catalysts, such large‐scale gas‐phase processes are poorly suited for significantly smaller‐scale production of isotopically enriched vinyl acetate‐1‐ 13 C. Earlier variants of synthetic procedures with interexchange of vinyl groups were based on mercury catalysis, which had some obvious disadvantages of toxicity and laborious workup. Another potential alternative is based on the recent advances in ruthenium‐based catalysis . However, the equilibrium between vinyl acetate‐1‐ 13 C and its unlabeled counterpart was not directly amenable to the preparation of vinyl acetate‐1‐ 13 C.…”
Section: Methodsmentioning
confidence: 99%
“…While vinyl acetate is industrially produced by vapor‐phase acetoxylation of ethylene over Pd‐based catalysts, such large‐scale gas‐phase processes are poorly suited for significantly smaller‐scale production of isotopically enriched vinyl acetate‐1‐ 13 C. Earlier variants of synthetic procedures with interexchange of vinyl groups were based on mercury catalysis, which had some obvious disadvantages of toxicity and laborious workup. Another potential alternative is based on the recent advances in ruthenium‐based catalysis . However, the equilibrium between vinyl acetate‐1‐ 13 C and its unlabeled counterpart was not directly amenable to the preparation of vinyl acetate‐1‐ 13 C.…”
Section: Methodsmentioning
confidence: 99%
“…It is evident that (I) exhibits a slightly higher activity (TOF = 36.3 h À1 and TON 4h = 113) in transvinylation catalysis compared with the structurally analogous complex (III) (TOF = 29.1 h À1 and TON 4h = 70.9), indicating a beneficial effect of bridging perfluoroheptanoate over bridging propionate ligands. The activity of (I) is similar to that of (IV) (TOF = 38.5 h À1 and TON 4h = 105), but lower than that of (II) (TOF = 153 h À1 and TON 4h = 205), which is the most active transvinylation catalyst to date in this model system (see Ziriakus et al, 2013).…”
Section: Tablementioning
confidence: 64%
“…Single molecules are connected via the terminal DMSO ligands, which show weak interaction with the CH 3 , CF 2 and CO groups of neighbouring molecules to form an alternating chain structure. A recent study by our group reports on the relevance of ruthenium carbonyl carboxylates for transvinylation (Ziriakus et al, 2013). Even though dinuclear sawhorse-type Ru complexes were found to exhibit mediocre activity compared with mononuclear compounds, a change in activity due to the electronic effect of the fluorination of the bridging carboxylate ligands may be anticipated.…”
Section: Tablementioning
confidence: 93%
“…A single‐crystal X‐ray structure analysis of Ru 2 (CO) 4 (μ‐O 2 C n Bu) 2 (P t Bu 3 ) 2 indicated that the complex had a bridging Ru 2 (CO) 4 backbone in a sawhorse‐type arrangement with two μ 2 ,η 2 ‐carboxylato bridges and two axial phosphine ligands . Since then, sawhorse‐type diruthenium complexes with carboxylato bridges have been synthesized and studied as catalysts,, for assembly of mesomorphic materials, as well as biologically active agents…”
Section: Introductionmentioning
confidence: 99%